PELAYANAN SAMSAT KELILING: CAPAIAN DAN TANTANGAN - Khoirun Nisa, Fajaria; Rimawati, Yuni (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2018)
This study aims to give an overview of SAMSAT mobile service as a public service. The focus of the discussion is on the achievement of the service that has been done by SAMSAT mobile services in North Surabaya and confirmed the achievement by asking the opinion of the taxpayer of the motor vehicle as the object of service. The methodology of this research is qualitative descriptive with triangulation data emphasizing on outcomes and challenges of SAMSAT mobile services in North Surabaya. The respondents of this research are 6 persons, 4 respondents are parties of UPT BPD North Surabaya East Java Province and 2 respondents are taxpayer of the motor vehicle. The conclusion of this research are: 1) the comprehensive target of SK achievement (Samsat Local and SAMSAT Link) has been reached in 2015 and 2016; 2) the existence of cost efficiency efforts; 3) the obstacles that often arise for the optimization of SAMSAT mobile services of North Surabaya is the administrative completeness and network problems; 4) SAMSAT mobile services of North Surabaya has socialized the administrative completeness that must be available in utilizing its services.